Economics of agroforestry: Links between nature and society - (:unkn) unknown (My University, 2023)
This special issue drew mainly from papers presented at the 4th World Congress on Agroforestry in France in 2019. It is intended as a contribution on the economic dimensions of agroforestry, embracing several scales, from the plot to the state, and several levels of socio-productive complexity. Through a pool of study cases carried out in several countries from four continents (Africa, Asia, Europe South America, and United States) the authors bring new light on the economic benefits of agroforestry, the need to improve its development worldwide, and the main socio-political determinants that explains agroforestry within territorial dynamics.
Keywords: African Research